Natural helper cells mediate respiratory syncytial virus-induced airway inflammation by producing type 2 cytokines in an IL-33-dependent manner. (August 2017) - Han, Xu; Chai, Ruonan; Qi, Feifei; Bai, Song; Cui, Yulin; Teng, Yuee; Liu, Beixing
Aim: Type 2 cytokine production during respiratory virus infection is considered to be linked with asthma exacerbation. As potent Th2 cytokine producers, natural helper (NH) cells play a key role in influenza virus-induced airway hyper-responsiveness. However, it is unclear whether NH cells contribute to respiratory syncytial virus (RSV)-induced airway inflammation, and how the cytokine profile in NH cells is changed during RSV infection.Methods: BALB/c mice were infected intranasally with RSV. The number of NH cells in lungs was detected by flow cytometry. The expression of cytokine mRNAs was performed by real-time RT-PCR. Cytokines levels were determined by ELISA.Results: Following intranasal infection with RSV, BALB/c mice showed an increase in the expression of mRNAs for Th2-like cytokines in NH cells. Furthermore, adoptive transfer of pulmonary NH cells resulted in a massive infiltration of mononuclear cells, in particular eosinophils and neutrophils in lungs, in parallel with an augmented production of Th2-associated cytokines, such as IL-4, IL-5 and IL-10 in bronchoalveolar lavage fluids, providing convincing evidence that NH cells contribute to RSV-induced lung pathogenesis by producing type 2 cytokines. It should be noted that blocking IL-33 with antibody can diminish the absolute number of pulmonary NH cells and the relative expression of mRNAs for type 2 cytokines in pulmonary NH cells, suggesting that IL-33 is necessary for activating Th2-type NH cells.Conclusion: These results reveal that pulmonary NH cells might participate in RSV-induced airway inflammation by producing large quality of type 2 cytokines in an IL-33-dependent manner.